Impact of a surface on the electro-reflectance spectra of n-Si(110) and their polarization anisotropy - Gentsar , P.O.; Vuichyk , M.V.; Stronski , A.V. (Physics and Chemistry of Solid State, 2020)
The electro-reflectance spectra, including their polarization dependencies were analyzed for n-Si(110) in the energy range of 2.9-3.8 eV. Based on the optical anisotropy of electro-optical effect, two contributions originated from a surface, (isotropic part relates to the linear electro-optical effect which inherent for (110) surface) and bulk, (anisotropic part relates to the Franz–Keldysh effect) were identified and separated. The presence of such extreme is explained by the zero value of the electron wave function on the surface and (or) the structure gettering of the free carriers.